Nanosheet hollow cluster, preparation method thereof, composite material and preparation method thereof
By preparing the hollow cluster structure of nanosheets and combining it with layered sheet materials, the problem of irregular size and difficulty in recycling of ternary metal chalcogen compounds in the field of photocatalysis in the prior art is solved, and the photocatalytic efficiency and recycling are improved , and efficient photoenergy absorption and reactant enrichment are achieved.
Patent Information
- Application Number
- CN202411332641.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-14
AI Technical Summary
In the preparation of ternary metal chalcogenides, the prior art has problems such as irregular size, difficulty in recycling, complex preparation process and environmental pollution, which affects its application efficiency and recycling rate in the field of photocatalytics.
The nanosheet hollow cluster structure is used, composed of ternary metal chalcogenide compounds, and the nanosheet hollow clusters are prepared by hydrothermal treatment and combined with layered sheet-like materials to form a composite material to improve photocatalytic performance.
The catalytic efficiency and recycling rate of the photocatalyst are improved, the light energy absorption capacity and reactant enrichment capacity are enhanced, the light shielding effect is reduced, and the hollow clusters of nanosheets are easy to be recovered and reused.
Smart Images

Figure CN119303608A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of nanomaterials, and in particular, to hollow nanosheet clusters and preparation methods thereof, composite materials and preparation methods thereof. Background Art
[0002] Ternary metal chalcogenides and polymetallic chalcogenides have many advantages over binary metal chalcogenides, such as narrower band gaps than metal oxide semiconductors, high light absorption coefficients, and generally better photostability, chemical stability, and electrical conductivity than binary metal sulfides. Their chemical composition is highly tunable, with more possible reactive sites, and the preparation method is relatively simple. Among them, ternary metal chalcogenides composed of one or more elements in the first subgroup, one or more elements in the third main group, and one or more elements in the sixth main group of the periodic table, namely IB-IIIA-chalcogenides, have been widely used in the field of thin-film solar cells. In addition, because IB-IIIA-chalcogenides have semiconductor characteristics and excellent photoelectric properties, they also have great development potential in the field of photocatalysis. Summary of the invention
[0003] In a first aspect of the present application, the present application proposes a hollow cluster of nanosheets, wherein the nanosheets are stacked to form a hollow cluster structure, wherein the hollow cluster structure has a cavity, wherein the nanosheets include a ternary metal chalcogenide.
[0004] The hollow clusters of nanosheets proposed in the present application have a nanocluster structure and a hollow structure formed by the accumulation of nanosheets, and therefore have a higher specific surface area. As a photocatalyst, they can enrich more reaction substances and improve the light scattering and light energy absorption utilization rate.
[0005] In some embodiments, the chemical formula of the ternary metal chalcogenide satisfies A a B b X c , wherein A includes group IB elements, B includes group IIIA elements, X includes chalcogen elements, 0<a<10, 0<b<10, 0<c<10. Therefore, the ternary metal chalcogenide has the characteristics of low toxicity, narrow band gap, and large light absorption coefficient, and has a wide range of application scenarios as a photocatalyst.
[0006] In some embodiments, the side length of the nanosheet is 40nm-60nm, and the thickness of the nanosheet is 5nm-15nm. Thus, within the aforementioned range of the side length and thickness of the nanosheet, the nanosheet and the hollow nanosheet cluster have a higher specific surface area.
[0007] In some embodiments, the particle size of the nanosheet hollow clusters is 200nm-400nm. Therefore, within the particle size range of the aforementioned nanosheet hollow clusters, it is beneficial to recycle the nanosheet hollow clusters after using them as photocatalysts.
[0008] In the second aspect of the present application, the present application proposes a method for preparing hollow clusters of nanosheets, comprising: mixing an aqueous solution of a Group IB metal salt and an aqueous solution of a Group IIIA metal salt to obtain a mixed solution, wherein the volume ratio of the aqueous solution of the Group IB metal salt to the aqueous solution of the Group IIIA metal salt is (1-3):(3-1); adding an aqueous solution of a crystallization directing agent dropwise to the mixed solution to obtain a mixed reaction liquid, wherein the volume ratio of the aqueous solution of the crystallization directing agent to the mixed solution is (1-3.75):(1-3); adding an aqueous solution of a sulfide substance dropwise to the mixed reaction liquid to obtain a precursor solution, wherein the volume ratio of the aqueous solution of the sulfide substance to the mixed reaction liquid is (2-13):(8-27); and performing hydrothermal treatment on the precursor solution to obtain the hollow clusters of nanosheets.
[0009] The present application proposes a method for preparing hollow nanosheet clusters, wherein the hollow nanosheet clusters are prepared by hydrothermal treatment, and the hollow nanosheet clusters have a microscopic morphology of clustered clusters. Under the same chemical composition, the hollow nanosheet clusters have a larger nanocrystal and quantum dot size in their structure, and a larger specific surface area, so they have a higher catalytic efficiency when used as photocatalysts.
[0010] In some embodiments, the temperature of the hydrothermal treatment is 150° C.-220° C., and the time of the hydrothermal treatment is 3 h-24 h. Thus, the reactants can form a nanosheet hollow cluster microstructure that is clustered and has a cavity.
[0011] In some embodiments, the molar concentration of the chalcogenide aqueous solution is 0.1 mol / L-0.5 mol / L.
[0012] In some embodiments, the molar concentration of the aqueous solution of the Group IB metal salt is 0.01 mol / L-0.5 mol / L.
[0013] In some embodiments, the molar concentration of the aqueous solution of the Group IIIA metal salt is 0.01 mol / L-0.5 mol / L.
[0014] In some embodiments, the molar concentration of the crystallization directing agent aqueous solution is 0.5 mol / L-1 mol / L. Thus, metal ions can form coordination bonds with the crystallization directing agent to control the morphology of the hollow nanosheet clusters.
[0015] In some embodiments, the dripping rate is 1 mL / min-3 mL / min, thereby better controlling the concentration of the crystallization directing agent.
[0016] In some embodiments, the crystal directing agent includes at least one of mercaptoacetic acid, mercaptopropionic acid, mercaptobutyric acid, selenoacetic acid, selenopropionic acid, selenobutyric acid, tellurylacetic acid, tellurylpropionic acid, tellurylbutyric acid, thioacetamide, thiourea, cysteine, selenoacetamide, selenourea, selenocysteine, tellurourea, and tellurocysteine. Thus, the crystal directing agent can coordinate with Group IB metal ions, Group IIIA metal ions, and chalcogen elements, with the chalcogen elements as the coordinating atoms.
[0017] In some embodiments, the Group IB metal salt includes at least one of fluoride salts, chloride salts, bromide salts, iodide salts, astatine salts, sulfites, sulfates, nitrites, nitrates, phosphates, oxalates, and acetates of Group IB elements. Thus, the Group IB metal salt can release Group IB metal ions.
[0018] In some embodiments, the Group IIIA metal salt includes at least one of fluoride salts, chloride salts, bromide salts, iodide salts, astatine salts, sulfites, sulfates, nitrites, nitrates, phosphates, oxalates, and acetates of Group IIIA elements. Thus, the Group IIIA metal salt can release Group IIIA metal ions.
[0019] In some embodiments, the Group IB metal salt includes at least one of chloride, sulfite, sulfate, nitrate, oxalate, and acetate of a Group IB element.
[0020] In some embodiments, the Group IIIA metal salt includes at least one of chloride, sulfite, sulfate, nitrate, oxalate, and acetate of a Group IIIA element.
[0021] In some embodiments, the chalcogenide includes at least one of thioacetamide, thiourea, cysteine, sodium sulfite, sodium sulfide, elemental sulfur, selenoacetamide, selenourea, selenocysteine, sodium selenite, sodium selenide, selenium dioxide, elemental selenium, tellurium urea, telluric acid, sodium telluride, sodium tellurite, sodium telluride, tellurium dioxide, and elemental tellurium. Thus, the chalcogenide can release chalcogen elements.
[0022] In the third aspect of the present application, the present application proposes a composite material, comprising: a lamellar material, wherein the lamellar material comprises graphite-like carbon nitride, nitrogen-doped graphene, a covalent triazine framework, tungsten nitride, nitrogen-doped Ti 3 C 2Tx, x includes at least one of -OH, -O, -F and at least one of boron nitride; there are hollow nanosheet clusters on the periphery of the lamellar material, and the hollow nanosheet clusters include the hollow nanosheet clusters proposed in the present application, or the hollow nanosheet clusters prepared by the method for preparing hollow nanosheet clusters proposed in the present application.
[0023] The composite material proposed in this application realizes the combination of lamellar material and hollow nanosheet clusters in space, so that the composite material has more space to accommodate and enrich reactants as a photocatalyst. At the same time, the lamellar material and the hollow nanosheet clusters are combined to form a heterojunction, so that the ability to absorb light energy is improved.
[0024] In a fourth aspect of the present application, the present application proposes a method for preparing the composite material proposed in the present application, comprising: subjecting a lamellar material to ultrasonic treatment in an ethanol solution, wherein the ultrasonic treatment time is 0.5h-1.5h; mixing an aqueous solution of a Group IB metal salt and an aqueous solution of a Group IIIA metal salt to obtain a mixed solution, wherein the volume ratio of the aqueous solution of the Group IB metal salt to the aqueous solution of the Group IIIA metal salt is (1-3):(3-1); dropping an aqueous solution of a crystallization directing agent into the mixed solution to obtain a mixed reaction solution, wherein , the volume ratio of the crystallization directing agent aqueous solution to the mixed solution is (1-3.75):(1-3); the sulfide substance aqueous solution is added dropwise to the mixed reaction liquid to obtain a precursor solution, wherein the volume ratio of the sulfide substance aqueous solution to the mixed reaction liquid is (2-13):(8-27); the lamellar material and the precursor solution are mixed in a mass ratio of (0.002-0.01):1 to obtain a composite material reaction liquid; the composite material reaction liquid is subjected to a hydrothermal treatment to obtain the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0026] Figure 1 This is a scanning electron microscope (SEM) image of the hollow nanosheet clusters of Example 1 of the present application;
[0027] Figure 2 This is a scanning electron microscope (SEM) image of the hollow nanosheet clusters of Example 1 of the present application;
[0028] Figure 3 It is a graph of ultraviolet-visible diffuse reflectance (UV-Vis DRS) of the hollow nanosheet clusters of Example 1 of the present application and the composite material of Example 5;
[0029] Figure 4This is a SEM image of the hollow nanosheet clusters of Example 2 of the present application;
[0030] Figure 5 This is a SEM image of the hollow nanosheet clusters of Example 3 of the present application;
[0031] Figure 6 This is a SEM image of the hollow nanosheet clusters of Example 4 of the present application;
[0032] Figure 7 This is a SEM image of the composite material of Example 5 of the present application;
[0033] Figure 8 This is the SEM image of the material of Comparative Example 1 of the present application;
[0034] Fig. 9 This is the SEM image of the material of Comparative Example 2 of the present application;
[0035] Fig.10 This is the SEM image of the material of Comparative Example 3 of the present application;
[0036] Fig.11 This is a SEM image of the material of Comparative Example 4 of the present application;
[0037] Fig.12 This is a SEM image of the material of Comparative Example 5 of the present application;
[0038] Fig.13 This is the SEM image of the material of Comparative Example 6 of the present application;
[0039] Fig.14 This is a SEM image of the material of Comparative Example 7 of the present application;
[0040] Fig.15 The curve of hydrogen peroxide changing over time in the catalytic hydrogen peroxide preparation test of the nanosheet hollow clusters of Example 1 and the composite material of Example 5 of the present application;
[0041] Fig.16 This is a curve showing the change of hydrogen peroxide over time in the catalytic hydrogen peroxide preparation test of the materials of Comparative Examples 1 to 7 of the present application.
[0042] Description of reference numerals:
[0043] 1-Layered material; 2-Nanosheet hollow clusters; 3-Nanosheet hollow clusters grown around the layered material. DETAILED DESCRIPTION
[0044] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0045] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0046] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0047] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0048] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0049] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0050] The preparation methods of IB-ⅢA-chalcogenides include solid phase sintering, hot injection, solvothermal and hydrothermal methods. IB-ⅢA-chalcogenides with hollow structures can also be prepared by template method. However, the IB-ⅢA-chalcogenides prepared by the above methods have their own shortcomings. The IB-ⅢA-chalcogenides prepared by the solid phase method have micron-level sizes and irregular microscopic morphologies. The micron-level size is not conducive to the effective separation and transmission of photogenerated carriers, and the irregular morphology makes the material performance uneven on the one hand, and is not conducive to the subsequent modification, uniformity and mechanism analysis on the other hand. The IB-ⅢA-chalcogenides prepared by the hot injection method are usually nanocrystals or quantum dots, nanomaterials with small particle sizes. When the nanomaterial is used as a photocatalyst, after the catalytic process is completed, due to its small size and mass, the nanomaterial is difficult to recover by filtration, centrifugation and other methods, so the recycling rate is not high, which is easy to cause waste and has limited application prospects. The preparation of IB-ⅢA-sulfur compounds with hollow structures by hard template method has the disadvantages of complex preparation process, high cost, and easy environmental pollution. In addition, the process of removing the template agent may cause the change of the morphology of the hollow structure and the generation of crystal defects. The preparation of IB-ⅢA-sulfur compounds with hollow structures by soft template method has the disadvantages of poor template stability and easy influence by external conditions, which affects the stability and uniformity of the hollow structure in the prepared IB-ⅢA-sulfur compounds.
[0051] In a first aspect of the present application, the present application proposes a hollow cluster of nanosheets, wherein the nanosheets are stacked to form a hollow cluster structure, wherein the hollow cluster structure has a cavity, wherein the nanosheets include a ternary metal chalcogenide.
[0052] The hollow clusters of nanosheets proposed in the present application, wherein the ternary metal sulfide compound is photoexcited under the irradiation of a light source, generating photogenerated holes with oxidation ability and free electrons with reduction ability to catalyze reactants in contact with the hollow clusters of nanosheets, and play the role of a photocatalyst. The hollow clusters of nanosheets have a nanocluster structure and a hollow structure formed by the accumulation of nanosheets, and the transmission efficiency of photogenerated carriers is relatively high at the nanoscale; the nanosheet structure and the hollow structure can enrich more reaction substances, which is conducive to light scattering, thereby improving the absorption and utilization rate of light energy and the catalytic efficiency.
[0053] In some embodiments, the chemical formula of the ternary metal chalcogenide satisfies A a B b X c, wherein A includes group IB elements, B includes group IIIA elements, X includes chalcogen elements, 0<a<10, 0<b<10, 0<c<10. Therefore, the ternary metal chalcogenide has the characteristics of low toxicity, narrow band gap, and large light absorption coefficient, and has a wide range of application scenarios as a photocatalyst.
[0054] In some embodiments, the side length of the nanosheet is 40nm-60nm, and the thickness of the nanosheet is 5nm-15nm. Thus, within the side length and thickness range of the aforementioned nanosheet, the nanosheet and the hollow nanosheet cluster have a higher specific surface area, which is conducive to enriching more reactants and improving the catalytic efficiency as a photocatalyst.
[0055] In some embodiments, the particle size of the hollow clusters of nanosheets is 200nm-400nm. Thus, within the particle size range of the hollow clusters of nanosheets, the hollow clusters of nanosheets have good dispersibility, reduce the light shielding effect, and reduce the excessive band gap caused by quantum effect, so the hollow clusters of nanosheets have high light scattering ability and light absorption efficiency. In addition, within the aforementioned particle size range, the hollow clusters of nanosheets are more easily recovered by centrifugation or natural sedimentation, which is conducive to the recovery and reuse of the hollow clusters of nanosheets.
[0056] In the second aspect of the present application, the present application proposes a method for preparing hollow clusters of nanosheets, comprising: mixing an aqueous solution of a Group IB metal salt and an aqueous solution of a Group IIIA metal salt to obtain a mixed solution, wherein the volume ratio of the aqueous solution of the Group IB metal salt to the aqueous solution of the Group IIIA metal salt is (1-3):(3-1); adding an aqueous solution of a crystallization directing agent dropwise to the mixed solution to obtain a mixed reaction liquid, wherein the volume ratio of the aqueous solution of the crystallization directing agent to the mixed solution is (1-3.75):(1-3); adding an aqueous solution of a sulfide substance dropwise to the mixed reaction liquid to obtain a precursor solution, wherein the volume ratio of the aqueous solution of the sulfide substance to the mixed reaction liquid is (2-13):(8-27); and performing hydrothermal treatment on the precursor solution to obtain the hollow clusters of nanosheets.
[0057] The present application proposes a method for preparing hollow clusters of nanosheets, wherein the hollow clusters of nanosheets are prepared by hydrothermal treatment, and the hollow clusters of nanosheets have a microscopic morphology of clustered clusters. Under the same chemical composition, the structure of the hollow clusters of nanosheets aggregated in clusters has larger nanocrystals and quantum dot sizes, and a larger specific surface area. Furthermore, the hollow clusters of nanosheets also have cavities, which are conducive to enriching reactants. Therefore, when used as a photocatalyst, it has a higher catalytic efficiency. After the catalytic process is completed, the hollow clusters of nanosheets are more easily recovered by centrifugation or natural sedimentation, which is conducive to repeated use.
[0058] In some embodiments, the hydrothermal treatment is performed in a reactor, and the volume filling degree of the reactor is 30%-70%.
[0059] Within the volume filling range of the aforementioned reactor, it is beneficial for the hydrothermal treatment to achieve a higher preparation efficiency, and it is also beneficial for the hydrothermal treatment to be carried out in a relatively stable reaction environment, thereby reducing the phenomenon of overheating of the reaction.
[0060] In some embodiments, the temperature of the hydrothermal treatment is 150° C.-220° C., and the time of the hydrothermal treatment is 3 h-24 h. Thus, the reactants can form a nanosheet hollow cluster microstructure that is clustered and has a cavity.
[0061] In some embodiments, the molar concentration of the chalcogenide aqueous solution is 0.1 mol / L-0.5 mol / L. Thus, within the molar concentration range of the chalcogenide aqueous solution, the chalcogenide can release chalcogen elements in the mixed reaction solution, and further combine with the crystallization directing agent and the metal ion to form a complex, thereby reducing the generation of sulfur-containing impurities and facilitating the preparation of a ternary metal sulfide with a more stable structure.
[0062] In some embodiments, the molar concentration of the aqueous solution of the Group IB metal salt is 0.01 mol / L-0.5 mol / L.
[0063] In some embodiments, the molar concentration of the aqueous solution of the Group IIIA metal salt is 0.01 mol / L-0.5 mol / L.
[0064] In some embodiments, the molar concentration of the crystallization directing agent aqueous solution is 0.5 mol / L-1 mol / L. Thus, metal ions can form complexes with the crystallization directing agent, and the complexes aggregate, so that the ternary metal sulfide compound is formed at a specific position during the hydrothermal reaction to form a specific structure of the hollow clusters of nanosheets of the present application.
[0065] In some embodiments, the dripping rate is 1 mL / min-3 mL / min. Thus, within the aforementioned dripping speed range, the crystallization directing agent and the metal ions and chalcogen elements in the mixed solution can form a complex with a spatial structure, which is conducive to forming the spatial structure of the hollow clusters of nanosheets after hydrothermal treatment.
[0066] In some embodiments, the crystal directing agent includes at least one of mercaptoacetic acid, mercaptopropionic acid, mercaptobutyric acid, selenoacetic acid, selenopropionic acid, selenobutyric acid, tellurylacetic acid, tellurylpropionic acid, tellurylbutyric acid, thioacetamide, thiourea, cysteine, selenoacetamide, selenourea, selenocysteine, tellurourea, and tellurocysteine. Thus, the crystal directing agent can coordinate with Group IB metal ions, Group IIIA metal ions, and chalcogen elements, with the chalcogen elements as the coordinating atoms.
[0067] In some embodiments, the Group IB metal salt includes at least one of fluoride salts, chloride salts, bromide salts, iodide salts, astatine salts, sulfites, sulfates, nitrites, nitrates, phosphates, oxalates, and acetates of Group IB elements. Thus, the Group IB metal salt can release Group IB metal ions.
[0068] In some embodiments, the Group IIIA metal salt includes at least one of fluoride salts, chloride salts, bromide salts, iodide salts, astatine salts, sulfites, sulfates, nitrites, nitrates, phosphates, oxalates, and acetates of Group IIIA elements. Thus, the Group IIIA metal salt can release Group IIIA metal ions.
[0069] In some embodiments, the Group IB metal salt includes at least one of chloride, sulfite, sulfate, nitrate, oxalate, and acetate of a Group IB element.
[0070] In some embodiments, the Group IIIA metal salt includes at least one of chloride, sulfite, sulfate, nitrate, oxalate, and acetate of a Group IIIA element.
[0071] In some embodiments, the chalcogenide includes at least one of thioacetamide, thiourea, cysteine, sodium sulfite, sodium sulfide, elemental sulfur, selenoacetamide, selenourea, selenocysteine, sodium selenite, sodium selenide, selenium dioxide, elemental selenium, tellurourea, telluric acid, sodium telluride, sodium tellurite, sodium telluride, tellurium dioxide, and elemental tellurium. Thus, the chalcogenide can provide at least one of the chalcogenide elements: sulfur, selenium, and tellurium, or can provide at least one of -SH, -SeH, and -TeH.
[0072] In the third aspect of the present application, the present application proposes a composite material, comprising: a lamellar material, wherein the lamellar material comprises graphite-like carbon nitride, nitrogen-doped graphene, a covalent triazine framework, tungsten nitride, nitrogen-doped Ti 3 C 2Tx, x includes at least one of -OH, -O, -F and at least one of boron nitride; there are hollow nanosheet clusters on the periphery of the lamellar material, and the hollow nanosheet clusters include the hollow nanosheet clusters proposed in the present application, or the hollow nanosheet clusters prepared by the method for preparing hollow nanosheet clusters proposed in the present application.
[0073] The composite material proposed in the present application, the hollow clusters of nanosheets are anchored on the periphery of the lamellar material, forming a structural connection with the lamellar material. The composite material connected in the spatial structure in the aforementioned manner increases the specific surface area of the composite material compared to the stacking of lamellar materials. At the same time, the combination of the hollow clusters of nanosheets and the lamellar material reduces the surface area of the lamellar material blocked by the hollow clusters of nanosheets, so that the lamellar material can also be in more sufficient contact with the reactants during the catalytic process. The spatial combination of lamellar materials and hollow clusters of nanosheets allows the composite material to have more space to accommodate and enrich reactants as a photocatalyst. At the same time, the lamellar material combines with the hollow clusters of nanosheets to form a heterojunction, which promotes the separation of photogenerated carriers and improves the activity of photogenerated carriers. The lamellar material includes graphite-like carbon nitride, nitrogen-doped graphene, covalent triazine framework, tungsten nitride, boron nitride, nitrogen-doped Ti 3 C 2 Tx, x represents a functional group, and the functional group includes at least one of -OH, -O, and -F, and has conductivity. A portion of the photogenerated electrons on the nanosheet hollow clusters are transferred to the lamellar material, and the total amount of metal ions in the nanosheet hollow clusters that are reduced due to the electrons is reduced, so that the stability of the ternary metal sulfide compound in the nanosheet hollow clusters is improved. The lamellar material can form a binding effect between the central atom and the ligand with the IB group metal ions and / or the IIIA group metal ions in the ternary metal sulfide compound, so that the composite material not only has a higher specific surface area, but also can further improve the catalytic performance and compound stability of the composite material through the combination between the lamellar material and the nanosheet hollow clusters.
[0074] In a fourth aspect of the present application, the present application proposes a method for preparing the composite material proposed in the present application, comprising: subjecting a lamellar material to ultrasonic treatment in an ethanol solution, wherein the ultrasonic treatment time is 0.5h-1.5h; mixing an aqueous solution of a Group IB metal salt and an aqueous solution of a Group IIIA metal salt to obtain a mixed solution, wherein the volume ratio of the aqueous solution of the Group IB metal salt to the aqueous solution of the Group IIIA metal salt is (1-3):(3-1); dropping an aqueous solution of a crystallization directing agent into the mixed solution to obtain a mixed reaction solution, wherein , the volume ratio of the crystallization directing agent aqueous solution to the mixed solution is (1-3.75):(1-3); the sulfide substance aqueous solution is added dropwise to the mixed reaction liquid to obtain a precursor solution, wherein the volume ratio of the sulfide substance aqueous solution to the mixed reaction liquid is (2-13):(8-27); the lamellar material and the precursor solution are mixed in a mass ratio of (0.002-0.01):1 to obtain a composite material reaction liquid; the composite material reaction liquid is subjected to a hydrothermal treatment to obtain the composite material.
[0075] In some embodiments, the volume fraction of the ethanol solution is 50%-100%, and the solvent of the ethanol solution includes water.
[0076] In some embodiments, the hollow clusters of nanosheets or the composite material are used as photocatalysts, and the photocatalyst, deionized water, and sacrificial agent are subjected to a catalyst mixing treatment in a light-proof environment to obtain a catalyst solution; reactants are subjected to a reactant mixing treatment with the catalyst solution to obtain a reactant mixed solution; and the reactant mixed solution is subjected to a photocatalytic treatment under a xenon light source. Thus, in a light-proof environment, the photocatalyst and the reactants form a stable reaction system, and then fully react in a light environment. Photocatalysis can be used to achieve reactions such as oxygen catalysis to form hydrogen peroxide, carbon dioxide reduction, and pollutant degradation.
[0077] In some embodiments, the catalyst mixing treatment includes ultrasonic treatment with an ultrasonic time of 0.5 min to 5 min.
[0078] In some embodiments, the reactant mixing process includes stirring process and bubbling process, and the time of the reactant mixing process is 0 min-60 min, thereby making the reactant fully contact with the photocatalyst, which is conducive to the photocatalyst to exert its catalytic ability.
[0079] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.
[0080] Example 1
[0081] Mix 3.9 mL of a 0.1 mol / L silver nitrate aqueous solution and 3.9 mL of a 0.1 mol / L gallium nitrate aqueous solution to obtain a mixed solution, and stir for 5 minutes;
[0082] Add 3 drops of 0.64 mol / L thioglycolic acid aqueous solution to the mixed solution, and continue stirring for 2.5 min; continue to slowly and dropwise add 9.4 mL of 0.64 mol / L thioglycolic acid aqueous solution, and complete the addition within 5 min, and stir for 15 min to obtain a mixed reaction solution;
[0083] Slowly and dropwise add 7.8 mL of a 0.2 mol / L thioacetamide aqueous solution to the mixed reaction solution within 5 min, and stir for 30 min to obtain a precursor solution;
[0084] The precursor solution is subjected to hydrothermal treatment, and the volume filling degree is 50% in the polytetrafluoroethylene reactor liner; the reactor is then placed in a 180°C oven for hydrothermal reaction for 12 hours to prepare hollow nanosheet clusters; the obtained hollow nanosheet clusters are centrifuged, and after removing the supernatant, they are centrifuged and washed three times with an ethanol-water mixture, placed in a 60°C oven, and dried for 6 hours. The prepared hollow nanosheet clusters include AgGaS 2 ,refer to Figure 1-Figure 3 , the size uniformity of the hollow nanosheet clusters is good. Figure 3 The prepared nanosheet hollow clusters have an absorption edge in the visible light region.
[0085] Example 2
[0086] Example 2 is consistent with Example 1, except that the temperature of the hydrothermal treatment is 160°C. Figure 4 The prepared hollow nanosheet clusters have a hollow cluster structure of stacked nanosheets.
[0087] Example 3
[0088] Example 3 is consistent with Example 2, except that the sulfide substance aqueous solution used is a 0.30 mol / L thioacetamide aqueous solution. Figure 5The prepared hollow nanosheet clusters have a hollow cluster structure of stacked nanosheets.
[0089] Example 4
[0090] Example 4 is consistent with Example 1, except that the aqueous solution of Group IB metal salt used is copper nitrate, and the prepared nanosheet hollow clusters include CuGaS 2 ,refer to Figure 6 The size of the prepared hollow nanosheet clusters is small.
[0091] Example 5
[0092] Preparation of composite materials
[0093] Mix 3.9 mL of a 0.1 mol / L silver nitrate aqueous solution and 3.9 mL of a 0.1 mol / L gallium nitrate aqueous solution to obtain a mixed solution, and stir for 5 minutes;
[0094] Add 3 drops of 0.64 mol / L thioglycolic acid aqueous solution to the mixed solution, and continue stirring for 2.5 min; continue to slowly and dropwise add 9.4 mL of 0.64 mol / L thioglycolic acid aqueous solution, and complete the addition within 5 min, and stir for 15 min to obtain a mixed reaction solution;
[0095] Slowly and dropwise add 7.8 mL of a 0.2 mol / L thioacetamide aqueous solution to the mixed reaction solution within 5 min, and stir for 30 min to obtain a precursor solution;
[0096] Graphite-like carbon nitride was used as a lamellar material for pretreatment. 400 mg of the lamellar material was added to 200 mL of ethanol-water mixture and ultrasonicated on ice for 1.0 h. The supernatant was removed by centrifugation and placed in an oven at 60°C for drying for 6 h.
[0097] 90 mg of the pretreated lamellar material was mixed with the precursor solution, and ultrasonicated for 1.5 min while stirring, and then the ultrasonication was stopped and stirring was continued for 30 min to obtain a composite material reaction solution;
[0098] Performing hydrothermal treatment on the composite material reaction liquid, transferring the composite material reaction liquid into a polytetrafluoroethylene reactor liner with a volume filling degree of 50%, placing the reactor in an oven at 180° C. for hydrothermal reaction for 12 hours to obtain a composite material;
[0099] The obtained composite material was centrifuged, the supernatant was removed, and then centrifuged and washed three times with an ethanol-water mixture, and then placed in an oven at 60°C for 6 hours. Figure 7The prepared material has the morphology of nanosheet hollow spherical clusters growing on the edge of the lamellar material. Figure 3 , the prepared composite material has an absorption edge in the visible light region.
[0100] Example 6
[0101] Example 6 is consistent with Example 5, except that 200 mg of the pretreated lamellar material is mixed with the precursor solution.
[0102] Example 7
[0103] Example 7 is consistent with Example 5, except that the lamellar material is nitrogen-doped graphene.
[0104] Comparative Example 1
[0105] Comparative Example 1 is consistent with Example 1, except that the sulfide substance aqueous solution used is a 0.05 mol / L thioacetamide aqueous solution. Figure 8 The prepared material is black, does not have the microscopic morphology of hollow nanosheet clusters, and has poor size uniformity.
[0106] Comparative Example 2
[0107] Comparative Example 2 is consistent with Example 1, except that the temperature of the hydrothermal treatment is 140°C. Fig. 9 The prepared material is black, does not have the microscopic morphology of hollow nanosheet clusters, and has poor size uniformity.
[0108] Comparative Example 3
[0109] Comparative Example 3 is consistent with Example 1, except that the precursor solution does not contain an aqueous solution of a Group IIIA metal salt, and the prepared material is Ag. 2 S. Reference Fig.10 , the prepared material does not have the microscopic morphology of hollow clusters of nanosheets.
[0110] Comparative Example 4
[0111] Comparative Example 4 is consistent with Example 1, except that the precursor solution includes magnesium nitrate and indium nitrate, and the prepared material is MgIn 2 S 4 . refer to Fig.11 , the prepared material does not have the microscopic morphology of hollow clusters of nanosheets.
[0112] Comparative Example 5
[0113] Comparative Example 5 is consistent with Example 5, except that 25 mg of the pretreated lamellar material is mixed with the precursor solution. Fig.12 In the prepared composite materials, the hollow spherical clusters of nanosheets have a higher proportion of wrapping the entire lamellar material.
[0114] Comparative Example 6
[0115] Comparative Example 6 is consistent with Example 5, except that the sheet-like processing material is first mixed with the mixed solution, and then thioglycolic acid and thioacetamide aqueous solutions are added in sequence. The prepared material is a mixture of dark green precipitate and yellow precipitate, generating silver sulfide, or a stoichiometric ratio of AgGaS 2 Different silver gallium sulfide compounds did not produce hollow nanosheet clusters. Fig.13 , the prepared material does not have a nanosheet hollow cluster structure.
[0116] Comparative Example 7
[0117] Comparative Example 7 is consistent with Example 5, except that amorphous carbon is used as the lamellar material. Fig.14 , the prepared material is an amorphous material structure.
[0118] Test method:
[0119] Catalytic hydrogen peroxide preparation test: Take 20 mg of the nanosheet hollow cluster powder photocatalyst prepared in Example 1 above in a 200 mL beaker, add 90 mL of deionized water, 10 mL of isopropanol and a magnetic stirrer, and place the beaker in an ice water bath after ultrasonic treatment for 3 minutes. Bubble pure oxygen for 20 minutes in a dark place (flow rate of 80 mL / min, stirring speed of 550 rpm), turn on the xenon light source for photocatalytic reaction, the illumination wavelength is 350nm-780nm, and the light power is 85mW / cm 2 . Thus, the nanosheet hollow cluster powder photocatalyst prepared by the present invention can be used to prepare hydrogen peroxide. The hydrogen peroxide yield can be determined by iodine titration in combination with a spectrophotometer. The specific operation is to take 2 mL of the reaction solution every 15 minutes, add 1 mL of A solution (aqueous solution of potassium iodide, ammonium molybdate and sodium hydroxide) and 1 mL of B solution (aqueous solution of potassium hydrogen phthalate) and mix them evenly, and then measure the absorbance with a spectrophotometer, and inversely calculate the concentration of hydrogen peroxide in the test solution by combining with a standard curve calibrated with a known concentration of hydrogen peroxide.
[0120] Cyclic catalytic test: After a single test of catalytic hydrogen peroxide preparation test, the nanosheet hollow cluster powder photocatalyst was recovered by centrifugation at 10,000 rpm for 10 min, and then put into use again after drying. The cycle was repeated 5 times.
[0121] Test results:
[0122] The hollow nanosheet clusters prepared in Example 1 and the composite material prepared in Example 5 were tested for catalytic hydrogen peroxide preparation. Fig.15 , both of which can produce hydrogen peroxide under photocatalysis.
[0123] The nanosheet hollow clusters prepared in Example 1 and the composite material prepared in Example 5 were subjected to cyclic catalytic tests.
[0124] The material prepared in Example 1 can produce hydrogen peroxide in five cycles under light, but the yield will decrease with the increase in the number of uses. The material prepared in Example 5 can produce hydrogen peroxide in five cycles under light, and its stability is higher than that of the material prepared in Example 1, and can produce hydrogen peroxide more stably in five cycles. The test data is shown in Table 1.
[0125] Table 1
[0126] Example 1 Example 5 First cycle 69.32μmol / L 127.40μmol / L Second cycle 54.96μmol / L 136.58μmol / L Third cycle 31.15μmol / L 113.69μmol / L Fourth cycle 26.22μmol / L 99.86μmol / L Fifth cycle 24.31μmol / L 110.68μmol / L
[0127] The hollow nanosheet clusters prepared in Comparative Examples 1 to 4 and the composite materials prepared in Comparative Examples 5 to 7 were tested for catalytic hydrogen peroxide preparation. Fig.16 It can be seen that in Comparative Examples 1, 3, and 6, the concentration of the aqueous solution of the sulfide substance, the composition of the prepared material, and the preparation method are changed respectively, so that the prepared material does not have the structure of the hollow clusters of nanosheets, and thus the catalytic ability is greatly reduced. In Comparative Examples 5 and 2, because the mass ratio of the lamellar material in the composite material is changed and the temperature of the hydrothermal treatment is changed respectively, the prepared material has a certain stacking structure, but does not have the structure of the hollow clusters of nanosheets, so the catalytic ability of the material is reduced to a certain extent. In Comparative Examples 4 and 7, the prepared materials are composite materials of ternary metal sulfide compounds composed of different metals and amorphous structures. The catalytic ability of the materials prepared in Comparative Examples 4 and 7 is somewhat different from the catalytic ability of the hollow clusters of nanosheets and the composite materials proposed in this application.
[0128] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.
[0129] In the description of this application, "same chemical composition" should be understood in a broad sense, that is, the main components of the two have the same chemical composition, or the chemical composition of the two is basically the same, and may have errors within the allowable range in the field that are understandable to those skilled in the art or contain impurities within the allowable range.
[0130] In the present application, the writing order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0131] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A hollow nanosheet cluster, characterized in that: The nanosheets are stacked to form a hollow cluster structure having a cavity, wherein the nanosheets include a ternary metal chalcogenide.
2. The hollow nanosheet cluster according to claim 1, characterized in that: The chemical formula of the ternary metal chalcogenide satisfies A a B b X c , wherein A includes group ⅠB elements, B includes group ⅢA elements, X includes chalcogen elements, 0<a<10, 0<b<10, 0<c<10.
3. The hollow nanosheet cluster according to claim 1 or 2, characterized in that: The side length of the nanosheet is 40nm-60nm, and the thickness of the nanosheet is 5nm-15nm; and / or, The particle size of the nanosheet hollow cluster is 200nm-400nm.
4. A method for preparing the hollow nanosheet clusters according to any one of claims 1 to 3, characterized in that: include: Mixing an aqueous solution of a Group IB metal salt and an aqueous solution of a Group IIIA metal salt to obtain a mixed solution, wherein the volume ratio of the aqueous solution of the Group IB metal salt to the aqueous solution of the Group IIIA metal salt is (1-3):(3-1); Adding a crystallization directing agent aqueous solution dropwise to the mixed solution to obtain a mixed reaction solution, wherein the volume ratio of the crystallization directing agent aqueous solution to the mixed solution is (1-3.75):(1-3); Adding the chalcogenide aqueous solution dropwise to the mixed reaction liquid to obtain a precursor solution, wherein the volume ratio of the chalcogenide aqueous solution to the mixed reaction liquid is (2-13):(8-27); The precursor solution is subjected to hydrothermal treatment to obtain the hollow nanosheet clusters.
5. The method according to claim 4, characterized in that The temperature of the hydrothermal treatment is 150° C.-220° C., and the time of the hydrothermal treatment is 3 h-24 h.
6. The method according to claim 4 or 5, characterized in that: The molar concentration of the chalcogenide aqueous solution is 0.1 mol / L-0.5 mol / L; and / or, The molar concentration of the aqueous solution of the Group IB metal salt is 0.01 mol / L-0.5 mol / L; and / or, The molar concentration of the aqueous solution of the IIIA group metal salt is 0.01 mol / L-0.5 mol / L.
7. The method according to claim 4 or 5, characterized in that: The molar concentration of the crystallization directing agent aqueous solution is 0.5 mol / L-1 mol / L; and / or, The dripping rate is 1 mL / min-3 mL / min; and / or, The crystal directing agent includes at least one of thioglycolic acid, thiopropionic acid, thiobutyric acid, selenoacetic acid, selenopropionic acid, selenobutyric acid, tellurylacetic acid, tellurylpropionic acid, tellurylbutyric acid, thioacetamide, thiourea, cysteine, selenoacetamide, selenourea, selenocysteine, tellurourea, and tellurylcysteine.
8. The method according to claim 4 or 5, characterized in that: The Group IB metal salt includes at least one of fluoride salts, chloride salts, bromide salts, iodide salts, astatine salts, sulfites, sulfates, nitrites, nitrates, phosphates, oxalates and acetates of Group IB elements; and / or, The Group IIIA metal salt includes at least one of fluoride salts, chloride salts, bromide salts, iodide salts, astatine salts, sulfites, sulfates, nitrites, nitrates, phosphates, oxalates, and acetates of Group IIIA elements; and / or, The sulfide substances include at least one of thioacetamide, thiourea, cysteine, sodium sulfite, sodium sulfide, elemental sulfur, selenoacetamide, selenourea, selenocysteine, sodium selenite, sodium selenide, selenium dioxide, elemental selenium, tellurium urea, telluric acid, sodium telluride, sodium tellurite, sodium telluride, tellurium dioxide, and elemental tellurium.
9. A composite material, characterized in that: include: Lamellar materials, wherein the lamellar materials include graphite-like carbon nitride, nitrogen-doped graphene, covalent triazine framework, tungsten nitride, nitrogen-doped Ti3C2Tx, where x includes at least one of -OH, -O, -F, and at least one of boron nitride; There are hollow nanosheet clusters on the periphery of the lamellar material, and the hollow nanosheet clusters include the hollow nanosheet clusters described in any one of claims 1 to 3, or the hollow nanosheet clusters prepared by the method described in any one of claims 4 to 8.
10. A method for preparing the composite material according to claim 9, characterized in that: include: In an ethanol solution, subjecting the lamellar material to ultrasonic treatment for a period of 0.5 h to 1.5 h; Mixing an aqueous solution of a Group IB metal salt and an aqueous solution of a Group IIIA metal salt to obtain a mixed solution, wherein the volume ratio of the aqueous solution of the Group IB metal salt to the aqueous solution of the Group IIIA metal salt is (1-3):(3-1); Adding a crystallization directing agent aqueous solution dropwise to the mixed solution to obtain a mixed reaction solution, wherein the volume ratio of the crystallization directing agent aqueous solution to the mixed solution is (1-3.75):(1-3); Adding a chalcogenide aqueous solution dropwise to the mixed reaction liquid to obtain a precursor solution, wherein the volume ratio of the chalcogenide aqueous solution to the mixed reaction liquid is (2-13):(8-27); The lamellar material and the precursor solution are mixed at a mass ratio of (0.002-0.01):1 to obtain a composite material reaction solution; The composite material reaction liquid is subjected to hydrothermal treatment to obtain the composite material.